PENGARUH IKLIM ORGANISASI DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI DI KEMENTERIAN KABUPATEN PANDEGLANG - Amin Hidayat; Irwan Maulana (Institut Ummul Quro Al-Islami Bogor, 2023)
This research focuses on how job climate and employability affect employee performance. The stratified random sampling method was used to select 99 employees. Research resultsshowed that ability and organizational environment simultaneously have a positive and significant effect on employee performance, with a coefficient of determination of 80.1%. Coefficient of determination of 80.1%. In addition, company capabilities and organizational environment affect employee performance partially and significantly. Apparently, of the two influential variables, the ability variable has the greatest influence. influence. Increasing work ability through training that is more in line with training is needed to improve employee performance. Relationships between individuals should also be improved to improve the work environment